TA`TSIRU ISTIKHDAAMU AL-WASIILAH AT-TA’LIMIYYAH LU’BAH AL-MURABBA’AT FII ISTII’AAB MUFRADAAT AL-LUGHAH AL-‘ARABIYYAH: DIRAASAH KAMIYYAH FII AL-MADRASAH AL-MUTAWASITHAH NURUL KASYYAF AL-ISLAMI BEKASI - Nurul Fahmi; Nabilah Fildzah (SHAWTUL ARAB, 2022)
The research was conducted in the middle school Noor Al-Kashf Al-Islami Bekasi in the second period of the academic year 2019-2020, starting from April 2020 to May 2020. Middle School Nur Al-Kashf Al-Islami Bekasi. The method used in this research is the experimental method. The community in this research includes all female students in the middle school, Noor Al-Kashf Al-Islami Bekasi, and the research samples are female students in the seventh semester, who number 70 students, and are divided into two classes, they are 35 students for the experimental class, and 35 students for the controlled class. In order to know the comprehension of the vocabulary of the Arabic language, the female students, the researcher used the final test, which is the written test. And the definition of this value after the tests are conducted, which is the normal test and the homogeneous test. As for the methods used to analyze the data, the t-test was used at the level of significance (0.05). Before doing the t-test, the researcher performs the natural test using Liliefors test. And the result of the normal test in the experimental class indicates that Lo (L account) is 0.136 and in the controlled class that Lo (L account) is 0.114 and L table for the experimental class is 0.886 (with samples of 35 students at the level of significance 0.05) and L table for the exact class is 0.886 (with samples of 35 students at the significance level 0.05). After knowing the normal test, it is indicated that Lo(L) is smaller than L. Accordingly, the table summarizes that the samples are normal. Without this, the homogeneous test uses the Bartlett test. From the result of the homogeneous test, 2X calculates 2,183>2X Table 3,841. Accordingly, the researcher summarizes that the data is homogeneous. In testing the hypothesis, the t calculation is 8.88 and the degree of freedom is 68. As for the t table of 1.67 at the level of importance (0.05), therefore the t calculation is 8.88 < t table 1.67, so the zero hypothesis (0H) is rejected, and the research hypothesis (1H) is accepted. In other words, there is a positive effect in the use of the educational method, the game of squares, in the comprehension of the vocabulary of the Arabic language among the students of the seventh class in the intermediate school, Nour Al-Kashf Al-Islami Bekasi. The result of the research indicates that the comprehension of the vocabulary of the Arabic language using the educational method, the game of squares, is higher and greater than the comprehension of the vocabulary of the Arabic language for students who were taught by the school without using the educational method, the game of squares.